Vaccine Literacy (Turkey Health Literacy Journal, 2022)
Vaccine literacy covers the individual’s knowledge, motivation and competence in accessing, understanding, evaluating and applying health information to make the right health decisions in daily life. An individual with advanced vaccine literacy accepts the vaccine as a must for a functioning health system, undertakes the task of vaccine advocacy in every environment and develops an uncomplicated system in order to ensure vaccine communication with other people. Old age is a very important period for vaccination literacy as well as vaccination. Lack of knowledge of the elderly population themselves or their caregivers; years of false traditions, myths and misperceptions; accessing services, using digital systems, and adapting to complex vaccination programs become more difficult with advancing age; combined with the deficiencies in the health records kept in the past years, it presents a difficult situation to overcome. The increase in susceptibility to infectious diseases, chronic diseases and cancers due to the weakening of the immune system requires vaccination literacy to be high both in the elderly group and among their families and caregivers. In this review, it is aimed to contribute to the writing by explaining the concepts of vaccine literacy, factors affecting vaccine literacy, vaccine hesitancy, vaccine rejection and vaccine communication.